“Loving Couples and Families:” Assimilation as Honorary Whiteness and the Making of the Vietnamese Refugee Family - Linh Thủy Nguyễn (Social Sciences, 2021)
Integration studies of Vietnamese refugees and their children begin with the problem of assimilation based on cultural and racial difference and ultimately lead these groups to achieve upward mobility against great odds. While scholars have offered alternatives to linear models of assimilation which assume a prescribed path to determine when migrants become integrated, the ideologies and norms which underlie the so-called problem of assimilation remain largely unexamined. Building from a feminist and Foucauldian analysis of power, this article examines state-sponsored knowledge production, such as semi-annual government surveys of Vietnamese refugees as representations which reproduce and reinforce logics of heteronormativity and white supremacy. I contextualize the production of these social science surveys as legibility projects in the geopolitical context of international (Cold War) and domestic (state attempts to dismantle black power movements through civil rights) maintenance of white supremacy. By examining self-sufficiency surveys of Vietnamese refugees conducted upon arrival to the US from the 1970s–1980s and 1990s studies of the second generation, I argue that the family is an instrumental yet overlooked dimension of the racialization of Vietnamese as new immigrants which is rooted in heteronormative, Orientalist, and anti-black notions of family.